2023
DOI: 10.3390/biomedicines11020256
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pharmacotherapeutic Profile of Patients with Type 2 Diabetes Mellitus Admitted to a Hospital Emergency Department

Abstract: Type 2 diabetes mellitus (T2DM) is closely associated with other pathologies, which may require complex therapeutic approaches. We aim to characterize the clinical and pharmacological profile of T2DM patients admitted to an emergency department. Patients aged ≥65 years and who were already using at least one antidiabetic drug were included in this analysis. Blood glycemia, creatinine, aspartate aminotransferase (AST), alanine aminotransferase (ALT), and hemoglobin were analyzed for each patient, as well as per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 112 publications
1
0
0
Order By: Relevance
“…The results were obtained from 50 T2DM patients undergoing sulfonylurea therapy, with a breakdown of 42% males and 58% females. These findings align with another similar study conducted by Lopes A, et al, where, in their research with a total of 420 randomly selected samples, data showed a higher percentage of women than men, specifically 51.4% women [10]. Distribution of age among T2DM patients at Dr. Soetomo Hospital during the period of June-September 2023 reveals that the majority fall within the Late Elderly group (56-65 years) at 38%, followed by the Early Elderly group (46-55 years) at 32%, and the Elderly (>65 years) at 20%.…”
Section: Discussionsupporting
confidence: 92%
“…The results were obtained from 50 T2DM patients undergoing sulfonylurea therapy, with a breakdown of 42% males and 58% females. These findings align with another similar study conducted by Lopes A, et al, where, in their research with a total of 420 randomly selected samples, data showed a higher percentage of women than men, specifically 51.4% women [10]. Distribution of age among T2DM patients at Dr. Soetomo Hospital during the period of June-September 2023 reveals that the majority fall within the Late Elderly group (56-65 years) at 38%, followed by the Early Elderly group (46-55 years) at 32%, and the Elderly (>65 years) at 20%.…”
Section: Discussionsupporting
confidence: 92%